Kajian Filsafat Hukum Tentang Hak Kampanye Pejabat Negara - Indra Budi Jaya (al-Battar: Jurnal Pamungkas Hukum, 2024)
The increasingly dynamic life of nationhood and statehood logically entails the demand to uphold basic ethical values and provide moral accountability for the ethics of state officials towards the public. The Campaign Right is a political right inherent to state officials, the implementation of which is regulated and supervised by a set of rules and legal instruments. The implementation of the campaign right by state officials, even though it has a basis in a positivistic and normative sense, often raises issues in practice considering that the position of rights will always be accompanied by obligations. The purpose of this research is to question how the right to campaign as a political right is viewed from the perspective of legal philosophy and how the moral (ethical) accountability of state officials who use the right to campaign is addressed. The research method in this study is qualitative and normative juridical with a philosophical approach and a statute approach that delves deeply into legal issues. The right to campaign is a political right that, from a positivistic and normative perspective, is certainly based on and sourced from the applicable regulations. In this case, the implementation of rights does not correspond with obligations, raising ethical and moral questions. Thus, even though the right to campaign for state officials is granted by law, it is bound by obligations that need to be prioritized. Even though accountability for the ethics and morals of state officials falls within the realm of relativity, which often intersects with political ethics—a domain that is open and vast—the demand for the implementation of state governance based on ethical and moral values is something that needs to be considered.